25. The Veps language in Russia: ELDIA Case-Specific Report - Grünthal, Riho; Puura, Ulriikka; Zajceva, Nina; Karjalainen, Heini
Report about the case study on the Veps language in Russia, conducted within the EU-FP7 research project ELDIA